Evaluation of Modeling Approaches for MILD Combustion Systems With Internal Recirculation - Amaduzzi, Ruggero; Ceriello, Giuseppe; Ferrarotti, Marco; Sorrentino, Giancarlo; Parente, Alessandro (Frontiers in Mechanical Engineering, 2020)
Numerical simulations employing two different modeling approaches are performed and validated against experimental results from a Moderate or Intense Low-Oxygen Dilution (MILD) system with internal recirculation. The FGM and PaSR closures are employed in a RANS framework to carry out the numerical simulations. The results show that FGM model strongly overpredicts temperature profiles in the reactive region, while yielding better results along the central thermocouple. The PaSR closure based on a prescribed mixing time constant, 𝐶!"#, of 0.01, 0.1 and 0.5 results are compared, showing that a 𝐶!"# value of 0.5 is the most appropriate choice for the cases under investigations. A PaSR formulation allowing to locally estimate the 𝐶!"# value is found to provide improved results for both the lateral and central thermocouples. A flame index analysis, used to assess the ability of FGM and PaSR to capture intense mixing of the cyclonic burner, indicates how the FGM model predicts a typical non-premixed region after the injection zone, contrary to the experimental observation.